2015
DOI: 10.1073/pnas.1512328112
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio optimization of phonon drag effect for lower-temperature thermoelectric energy conversion

Abstract: Although the thermoelectric figure of merit zT above 300 K has seen significant improvement recently, the progress at lower temperatures has been slow, mainly limited by the relatively low Seebeck coefficient and high thermal conductivity. Here we report, for the first time to our knowledge, success in first-principles computation of the phonon drag effect-a coupling phenomenon between electrons and nonequilibrium phonons-in heavily doped region and its optimization to enhance the Seebeck coefficient while red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
99
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 51 publications
5
99
0
1
Order By: Relevance
“…In a later study using a full first-principles calculation with both electron and phonon relaxation times extracted from DFT calculations, the Seebeck coefficient including the phonon drag was predicted with excellent agreements compared to the experiment [126], as shown in Fig. 11a.…”
Section: Seebeck Coefficientmentioning
confidence: 68%
See 4 more Smart Citations
“…In a later study using a full first-principles calculation with both electron and phonon relaxation times extracted from DFT calculations, the Seebeck coefficient including the phonon drag was predicted with excellent agreements compared to the experiment [126], as shown in Fig. 11a.…”
Section: Seebeck Coefficientmentioning
confidence: 68%
“…It was shown that at room temperature in lightly-doped n-type (p-type) silicon the phonon drag contribute to 30% (40%) of the total Seebeck coefficient [126]. As we have mentioned, phonon drag effect can be understood as the momentum transfer from non-equilibrium phonons with long mean free paths to the electron system.…”
Section: Seebeck Coefficientmentioning
confidence: 95%
See 3 more Smart Citations